2003
DOI: 10.1097/00005373-200301000-00020
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Trauma Management and Its Impact on Surgical Resident Training

Abstract: Our residency program had 10 graduating chief residents over the 3-year time period. With only 64 operative trauma cases, this yields an average of 6.4 trauma cases per resident. This falls significantly short of the 16-case minimum requirement in trauma surgery established by the RRC. The operative trauma requirements established by the RRC for graduating residents may be unattainable in many residency programs because of the high incidence of blunt trauma and the changing patterns of trauma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 2 publications
0
45
0
1
Order By: Relevance
“…In a large series from a statewide database from North Carolina improved outcome in patients with blunt abdominal trauma was observed over a 5-year period [6]. As particularly in level I trauma centers an increased incidence of these injuries was observed over the same period, it was concluded that increased experience in caring for these patients [6] and in the use of CT scanning and focused abdominal sonography for trauma [4,36]. The employment of more strictly defined indications for surgery in case of hemodynamic stability were described as one of the most significant changes in the treatment strategies of these patients [6,20,37].…”
Section: Number Of Late Deaths (> 24 H After Trauma) (% Of N)mentioning
confidence: 99%
“…In a large series from a statewide database from North Carolina improved outcome in patients with blunt abdominal trauma was observed over a 5-year period [6]. As particularly in level I trauma centers an increased incidence of these injuries was observed over the same period, it was concluded that increased experience in caring for these patients [6] and in the use of CT scanning and focused abdominal sonography for trauma [4,36]. The employment of more strictly defined indications for surgery in case of hemodynamic stability were described as one of the most significant changes in the treatment strategies of these patients [6,20,37].…”
Section: Number Of Late Deaths (> 24 H After Trauma) (% Of N)mentioning
confidence: 99%
“…The issue of limited ongoing experience is also apparent to trainees who have increasingly deflected away from making career choices to become trauma surgeons. 19 These 2 dominant issues (operative case load and skill maintenance) have been significant factors in the development of ACS services in the United States. 8,[18][19][20] In Canada, one can make a similar argument that in centres where ACS is not directly integrated with the trauma service owing to volume concerns (most centres), maintenance of skills must be maintained by active involvement in a critical threshold of ACS service weeks and complex cases.…”
Section: Yearmentioning
confidence: 99%
“…This concern has been raised by Bullinski who suggested simulation, inanimate models and anything else that the future may offer. 29 However our residents due to the sheer workload of associated general surgery both elective and emergency are able to circumvent this fall out now and for next many more years to follow.…”
Section: Radjou An Et Al Int Surg J 2015 Nov;2(4):527-533mentioning
confidence: 99%